Ethnoconservation of fishery resources in the Sapuka Islands, South Sulawesi Province, Indonesia - ANDI NUR APUNG MASSISENG; LUKMAN DARIS; MUHAMMAD FARID SAMAWI; JAYA JAYA; IRWANSYAH IRWANSYAH; ST. ZAENAB (Society for Indonesian Biodiversity, 2023)
Abstract. Massiseng ANA, Daris L, Samawi MF, Jaya J, Irwansyah, Zaenab S. 2023. Ethnoconservation of fishery resources in the Sapuka Islands, South Sulawesi Province, Indonesia. Biodiversitas 24: 6461-6471. One form of sustainable management of fishery resources is establishing ethnoconservation-based zoning to create a more targeted utilization practice. Therefore, this research aimed to determine the types of ethnoconservation, analyze the distribution of fishery resources, and create ethnoconservation-based zoning in the Sapuka Islands, South Sulawesi Province, Indonesia. The novelty of this research was that it combined regional ethnoconservation-based zoning in the Sapuka Islands community and zoning designated by government regulations. Data was collected through observation, in-depth interviews, Participatory Rural Appraisal (PRA), social mapping and taking coordinate points using the Global Positioning System (GPS) in the waters of the Sapuka Islands. The results showed that ethnoconservation practices related to community culture included restrictions on fishing times and a ban on catching several types of species. Meanwhile, a prohibition based on local regulations restricted fishing gear in certain water areas and prohibited damage to coral reefs. About 18 species of fishery resources were found widespread across the waters of the Sapuka Islands. There is an overlapping area between the ethnoconservation zone of local communities and the conservation zone based on the decree of the Minister of Maritime Affairs and Fisheries with an extent of 2,293.01 ha. This area can be recommended as the conservation zone, which is mutually agreed upon by both local communities and the government.